Motivation in second language acquisition among learners in Malaysia - Sorayyaei Azar, Ali; Tanggaraju, Darshini (Studies in English language and education, 2020)
Lack of motivation is the critical factor which affects university students’ learning process in Malaysia. Hence, this study is an attempt to investigate the types of motivation which Bachelor students used in learning English at one of the private universities in Malaysia. It was also analysed to determine the motivational level of the Bachelor students who learn English as a Second Language (ESL). This study used a quantitative method where the data was collected through the questionnaire adapted from Gardner’s (1972) Attitude, Motivation Test Battery (AMTB). The questionnaire was distributed to 150 students and the data was analysed quantitatively. The findings showed that the majority of the Bachelor students were instrumentally motivated towards learning ESL. The result concerning the level of motivation showed that the students had a high level of instrumental motivation for learning English, compared to integrative, resultative, and intrinsic ones. Yet, it is also apparent that all four types of motivation are at a high motivational level. Based on the findings, a few suggestions were highlighted. First, the lecturers should always design a classroom environment that promotes students’ motivation towards learning ESL. Second, students should be given more opportunities to visit other English native countries under Global Learning Programmes (GLP). In that case, teachers or lecturers of ESL should promote all types of motivation in the classroom and guide students towards achieving goals.